An Analysis of Fromm’s Five Basic Needs on Danny Boodman T.D. Lemon 1900 in The Legend of 1900 Movie - PUTRI RINDU KINASIH (Faculty of Language and Literature, University of Surakarta, 2023)
How people behave and carry out their will is influenced by psychological factors. Ascertaining the cause of maladaptation, therefore, the psychoanalytic study is necessary. In this research, the writer analyzes the character of Danny Boodman, T.D. Lemon 1900 and his drastic decision in life. The writer used the qualitative method. The writer focuses on the theory of five basic human needs proposed by Erich Fromm. Moreover, according to the findings, people who do not meet Fromm's five essential human needs will struggle to lead everyday lives. According to Fromm, there are two ways to resolve the existential dilemma: to progress or to regress to the mother's love and its evolutionary equivalent, a symbiotic relationship with the mother. The SS Virginian cruise ship is a metaphor for a mother's love of rootedness. Thus, this study concludes that Nineteen Hundred cannot achieve Fromm's five basic needs due to his obsession with the ship.